The cost of dialysis in low and middle-income countries: a systematic review. Issue 1 (June 2015) - Mushi, Lawrencia; Marschall, Paul; Fleßa, Steffen
Abstract Background The cost of dialysis in low and middle-Income countries has not been systematically reviewed. The objective of this article is to systematically review peer-reviewed articles on the cost of dialysis across low and middle-income countries. Methods PubMed and Embase databases were searched for the year 1998 to March 2013, and additional studies were added from Google Scholar search. An article was included if two reviewers agreed that it had reported cost of dialysis from low and middle-Income countries. Results The annual cost per patient for hemodialysis (HD) ranged from Int$ 3, 424 to Int$ 42, 785, and peritoneal dialysis (PD) ranged from Int$ 7, 974 to Int$ 47, 971. Direct medical cost especially drugs and consumables for HD and dialysis solutions and tubing for PD were the main cost drivers. Conclusion The number of studies on the economics of dialysis in low and middle-income countries is limited. Few papers indicate that dialysis is an expensive form of treatment for the population of these countries and that the poorer countries have an over-proportional burden to finance dialysis services. Further research is needed to determine the cost of dialysis based on a standard methodology grounded on existing economic guidelines and to address the question whether dialysis should be an element of the essential package of health in resource-poor countries. Used data should be as complete as possible. In case of missing data, proxies can be used. In case of developing countries, expert interviews are often used for estimating missing information.